Extra-large Rare Parotid Sialolith - A Case Report and Review of Literature - Neelakamal Hallur; Aaisha Siddiqa; Syed Zakaullah; Chaitanya Kothari; Shereen Fatima; Manazir Hussain; Neha Mustare (RGUHS Journal of Dental Sciences)
Sialoliths comprising 30 of all salivary gland diseases can lead to excretory duct obstruction. Predominantly affecting the submaxillary gland 83 to 94 followed by the parotid 4 to 10 and sublingual glands 1 to 7 these concretions have an average size ranging from 6 to 9 mm. We present a case of 34-year-old male presented with an extra-large sialolith in the right parotid duct. The diagnosis was confirmed through clinical examination panoramic radiography OPG and CT scan. The treatment included intra-oral sialolithotomy along with the administration of oral antibiotics and analgesics. Parotid gland calculi typically unilateral and more prone to affect the duct than the gland itself are less prevalent than subman-dibular calculi. The choice of treatment for sialoliths depends on factors such as size and location.